Comparing the kinematic characteristics of the lower limbs in table tennis: Differences between diagonal and straight shots using the forehand loop - He, Y.; Lv, X.; Zhou, Z.; Sun, D.; Baker, J. S.; Gu, Y. (Journal of Sports Science & Medicine, 2020)
The diagonal shot (DS) and straight shot (SS) using the forehand loop are the most common techniques used in table tennis. The purpose of this study was to investigate the kinematic differences of the lower limbs between DS and SS. Twelve male table tennis athletes performed DS and SS in random order. Kinematic data were captured using a three-dimensional Vicon motion analysis system. The major findings of this study were that DS showed significantly less time compared with SS during the backward swing (BS) and the forward swing (FS) phases. Meanwhile, DS showed significantly larger ankle internal rotation and inversion with smaller knee abduction and external rotation during the BS. DS showed significantly larger knee extension with smaller hip adduction and knee internal rotation compared with SS during the FS. However, SS showed a significantly larger range of motion (ROM) of ankle plantar flexion external rotation, and significantly larger ROM of knee extension. Moreover, SS showed significantly larger knee internal rotation compared with DS. These differences between the two shot techniques could be beneficial for helping coaches and table tennis athletes optimize performance, both in training and competition.